Technology stress among university personnel in North Sulawesi. - Lenda Mambo (Economics and Digital Business Review, 2024)
The requirement of Pangkalan Data Pendidikan Tinggi Indonesia (PDDIKTI) to upload all university data and information to this web-site has created a certain kind of stress among its stakeholders. This study assesses the level of technology stress that academic staff members in an Indonesian university endure in dealing with this requirement. There were forty-five respondents of a Christian University in North Minahasa region- Sulawesi, Indonesia who participated in this study. As users of the university application system their degree of technology stress was assessed and measured, based on their occupation and their involvement in the stressors associated with technology, including technology overload, technology complexity, technology insecurity, and technology uncertainty. Descriptive statistics and Analysis of variance method were used to analyzed the data. Out of the twenty-three contributing factors that were examined, the study discovered that only four factors contributed to very high stress and six factors contributed to high stress. The remaining thirteen components were responsible for the mild to moderate stress. With a mean score of 2.40, the study concluded that the respondents exhibited moderate levels of technology stress overall. Technology overload has a mean of 2.86, technology uncertainty’s mean is 2.51, technology invasion’s mean is 2.38, technology complexity’s mean is 2.21, and technology insecurity’s mean is 2.02 are the contributors with the moderate level of stress. ANOVA analysis revealed no significant differences in the degree of technology stress experienced by the various users (p=0.94 > 0.05), but it did reveal significant differences in the degree of technology stress across contributors (p= 0.0025 < 0.05). The research praises the PDDIKTI for offering sufficient training and consistent socialization of its program to all stakeholders.